Group portrait of the attendees of the 1942 Mount Hermon Baptist Bible Conference - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Mount Hermon Baptist Bible Conference, held July 26 to August 2, 1940 at Mount Hermon, California.